Parenting Program Management: Fostering School-Parent Cooperation to Optimize Children's Character Development in Early Childhood Education - Erlina, Erlina; Bahrun, Bahrun; Ismail, Ismail (Heca Sentra Analitika, 2024)
This study investigates the management and implementation of parenting programs in early childhood education settings within Southwest Aceh, Indonesia. The research focuses on three kindergartens (TK), TK. Negeri Pembina Blangpidie, TK. Al Khaliq Susoh, and TK. Jamal Has Jeumpa—utilizing a qualitative approach to explore how these programs are planned, organized, executed, and monitored. Findings underscore the critical role of school principals in leading these initiatives and the significant impact of active parental involvement on children's character development. The study highlights the successful integration of community resources and stakeholder engagement despite resource constraints and cultural differences. The results suggest that systematic management, continuous feedback, and adaptive strategies are essential for effective collaboration between schools and parents. Key observations include the need for clear annual goals, structured coordination, and regular evaluation mechanisms to refine program effectiveness. The study calls for future research to address its limitations, including a confined geographical scope and short study duration, by conducting longitudinal and comparative studies across diverse regions. Incorporating quantitative methods alongside qualitative insights could provide a more comprehensive understanding of the long-term impacts of parenting programs on child development. Therefore, the research advocates for policies that facilitate active school-parent collaboration, emphasizing the importance of community involvement in educational practices to support the holistic development of children.